Chinese Politics in the Xi Jinping Era : Reassessing Collective Leadership - Li, Cheng (Book collections on Project MUSE., 2016)
Chinese politics are at a crossroads as President Xi Jinping amasses personal power and tests the constraints of collective leadership. In the years since he became general secretary of the Chinese Communist Party in 2012, Xi Jinping has surprised many people in China and around the world with his bold anti-corruption campaign and his aggressive consolidation of power. Given these new developments, we must rethink how we analyze Chinese politics#x97;an urgent task as China now has more influence on the global economy and regional security than at any other time in modern history. Chinese Politics.